Severe familial left ventricular non-compaction cardiomyopathy due to a novel troponin T (TNNT2) mutation - Lüdde, Mark; Ehlermann, Philipp; Weichenhan, Dieter; Will, Rainer; Zeller, Raphael; Rupp, Stefan; Müller, Andreas; Steen, Henning; Ivandic, Boris; Ulmer, Herbert E.; Kern, Michael A.; Katus, Hugo; et al. (Cardiovascular research, 2010)
Left ventricular non-compaction (LVNC) is caused by mutations in multiple genes. It is still unclear whether LVNC is the primary determinant of cardiomyopathy or rather a secondary phenomenon with intrinsic cardiomyocyte dysfunction being the actual cause of the disease. Here, we describe a family with LVNC due to a novel missense mutation, pE96K, in the cardiac troponin T gene (TNNT2).